POVERTY AND SOCIO-ECONOMIC DEVELOPMENT IN NSUKKA LOCAL GOVERNMENT AREA, ENUGU STATE , SOUTHEASTERN NIGERIA - Alphonsus Nwachukwu, Ali; Ogechi, Agbiogwu (Innovare Journal of Social Sciences, 2014)
The study examined the incidence of poverty and socio-economic development in Nsukka Local Government Area (LGA) in Enugu State of Nigeria. . The data for the study were obtained from primary and secondary sources. The primary sources were field observations, questionnaire survey and personal interviews. Thus, the data generated during the course of the study were analyzed using statistical techniques of Poverty Headcount Index (PHI), Availability Index and Spearman's Correlation Analysis. The results of the Poverty Headcount Index shows that the level of poverty in Nsukka LGA is 69.2%, representing a poverty headcount index of 0.692, while the results of the composite Availability Index reveals that the level of socio-economic development is low, with a composite availability Index of 580. On the other hand, the result of the Spearman's Rank Correlation analysis shows that the correlation coefficient between poverty and socio-economic development is -0.95 which is very high, negative and significant at 5% probability level. Therefore, based on the results of the findings of the study, we suggest that the development of human capital, and the provision and sustenance of infrastructural facilities and social amenities such as road network, electricity and water supply, will go a long way in combating poverty and fostering socio-economic development in the area. Keywords: Poverty, Development, Relationship, Nsukka.